Modification and Characterization of Alpha and Beta Nickel (II) Hydroxide - Safari, Reza (My University, 2018)
Nickel Hydroxide is one of highly active materials used in various energy conversion applications. One of the key factors in the deposition of Ni(OH)2 is the active surface area which plays an important role in improving the efficiency of transformation reactions. There are various methods to enhance the active area. One method that can be used to modify the morphology of deposited Ni(OH)2 is to generate porous structures. Ni(OH)2 can be formed in two different phases namely alpha and beta. The main objective in our work is to optimize the synthesis conditions and characterize structures at the nanoscale, and also demonstrate unequivocally the presence of alpha and beta phases. For this work, a combination of electron microscopy and electrochemistry is needed to modify the morphology of nickel hydroxide and for detailed structural characterization. Various characterization techniques are used to investigate different electrochemical depositions conditions of Ni(OH)2 in alpha and beta phase forms using Direct and Indirect methods, respectively. Kinetically, alpha-Ni(OH)2 is easier and faster to be synthesized and can be deposited directly in one step. During cyclic voltammetry of alpha-Ni(OH)2 in KOH, the volume of material involved in the oxidation reaction increases in every cycle. Scanning Electron Microscopy and Transmission Electron Microscopy characterization shows that this may be due to microbubble formation that transform deposited sheets to particulate shapes. On the other hand, conversion of nickel metal to beta-Ni(OH)2 during cyclic voltammetry causes an expansion of particles. Effectively, nickel hydroxide is formed on the shell while nickel remains in the core. High Resolution Transmission Electron Microscopy is then used to identify the distribution of these phases. Another foremost feature for the beta phase is to make nickel metal in any desired shape, which can then be converted to beta-Ni(OH)2 through Cyclic Voltammetry in KOH. The presence of both phases is demonstrated with electron diffraction. Finally, as future work, all experiments will be performed in-situ TEM using liquid cell to observe structural changes in real time.
I have submitted another pdf file which is my permissions for figures used in my thesis. The name this file is Clearance.
Keywords: Modification and Characterization of Alpha and Beta Nickel (II) Hydroxide